A facile synthesis of pH stimuli biocompatible block copolymer poly(methacrylic acid)-block-poly(N-vinylpyrrolidone) utilizing switchable RAFT agents. Issue 16 (29th March 2019) - Pan, Xiangyu; Guo, Xiaofeng; Choi, Bonnie; Feng, Anchao; Wei, Xiaohu; Thang, San H.
Abstract : Synthesis of block copolymer PMAA- b -PNVP utilizing switchable RAFT agents and its self-assembly. Abstract : This paper presents a facile synthesis of poly(methacrylic acid)- block -poly( N -vinylpyrrolidone) (PMAA- b -PNVP) block copolymer utilizing a stimuli responsive RAFT agent that can be switched to offer good control over the polymerisation of MAMs and LAMs. Commercially available acid/base switchable RAFT agents, e.g., 2-cyanopropan-2-yl N -methyl- N -(pyridine-4-yl)carbanodithioate, were used and the block copolymer PMAA- b -PNVP was obtained after the hydrolysis of the corresponding well-defined, low dispersity poly( t -butyl methacrylate)- block -poly( N -vinylpyrrolidone) (P( t -BMA)- b -PNVP). This block copolymer has an advantage over its random copolymer counterpart as it can self-assemble to form micelles under acidic conditions.